SCIENTIFIC-THEORETICAL VIEWS ON TERMS AND TERMINOLOGY IN LINGUISTICS - Djumambetova, Gulziba (Журнал иностранных языков и лингвистики, 2023)
This article deals with the scientific-theoretical views on terms and terminology in linguistics. The theoretical foundations of the terminology are also described. Moreover, it deals with the viewpoints of scientists on this topic and we also offer some types of classification for the definition of terms and terminology. This research paper critically examines the scientific-theoretical perspectives surrounding the concepts of terms and terminology within the field of linguistics. The study delves into the multifaceted nature of terms and terminology, investigating the varying viewpoints put forth by linguistic scholars, theoreticians, and practitioners. By analyzing the historical evolution, theoretical frameworks, and practical implications associated with terms and terminology, this research aims to provide a comprehensive understanding of their significance within the linguistics discipline. Employing a qualitative research approach, the study draws on an extensive literature review encompassing a range of linguistic theories and methodologies. The primary focus is on the conceptualization, classification, and utilization of terms and terminology in linguistics, spanning various subfields such as syntax, semantics, phonology, and sociolinguistics. The analysis aims to uncover commonalities and divergences among linguistic scholars' perspectives, as well as the contextual factors influencing the development and application of terminological systems. The research’s importance lies in its potential to contribute to the refinement of linguistic scholarship, education, and communication. By synthesizing and critiquing the diverse views on terms and terminology, the study can help establish a more cohesive theoretical foundation for linguistic terminology, addressing potential ambiguities and inconsistencies. Furthermore, the findings can inform the design of linguistic curricula, facilitating the teaching and learning of terminology in linguistics programs worldwide. Additionally, the research has implications for interdisciplinary collaboration and knowledge dissemination. Furthermore, the research's potential to inform pedagogical practices and interdisciplinary collaboration underscores its relevance for advancing linguistic scholarship and facilitating effective communication in both academic and practical contexts.